PENGARUH BEBAN PIUTANG TAK TERTAGIH TERHADAP RETURN ON ASSETS (Studi pada PT PLN (Persero) Distribusi Jawa Timur Area Malang pada Periode Tahun 2009-2016) - Nur Rositah; Siti Ragil Handayani (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
The study aimed to determine how much bad debts charged by the company and the leveingl of profitability achieved by the company at each end of the period, analyze and explain the significant effect of bad debts on the profitability of the company. This research is an associative research with survey approach. The object is PT.PLN (Persero) Distribution East Java Area Malang Period 2009-2016. The result of statistical test shows that bad debts have negative and significant effect on Return On Assets, it can be seen from simple linear regression test with coefficient value of -0.036, negative value which means there is an opposite relationship between variables bad debts with variable return on assets. Test results using t test show the significance value of 0.000 is smaller than 0.05 and the value of